1978
DOI: 10.1111/j.1365-2672.1978.tb04206.x
|View full text |Cite
|
Sign up to set email alerts
|

Airflows In and Around Linear Downflow ‘Safety’ Cabinets

Abstract: Schlieren photography has been used to visualize the airflows in and around three re‐circulating linear downflow cabinets. The results show that there is an air ‘bulge’ at the front opening that allows air from within the cabinet to spill out towards the operator. Hand movements within, and activity just outside, cause air to be expelled from these cabinets. Bunsen burners within the cabinets destroy the linear nature of the downflowing air streams. The results indicate that the operator protection afforded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Analysis of the explainable failings of the class II MSCs in the older laboratory (there were none for the HI/III MSC) shows these were due to three environmental factors: draughts induced by mechanisms disassociated with the MSC; sudden room pressure variations; and rapid movements in and out of, or about the MSC/testing equipment. These types of factors have been discussed elsewhere ( Clark & Mullan 1978; Rake 1978; Clark 1983b; Kennedy 1987; Clark et al . 1990 ; Kruse et al .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the explainable failings of the class II MSCs in the older laboratory (there were none for the HI/III MSC) shows these were due to three environmental factors: draughts induced by mechanisms disassociated with the MSC; sudden room pressure variations; and rapid movements in and out of, or about the MSC/testing equipment. These types of factors have been discussed elsewhere ( Clark & Mullan 1978; Rake 1978; Clark 1983b; Kennedy 1987; Clark et al . 1990 ; Kruse et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, the unit had a plenum that carried contaminated air under pressure, and McGarrity and Coriell (1974) described an improved version with the dirty air under negative pressure. Clark and Mullen (1978) visualised the airflows within units with glass walls by Schlieren photography. They noted that air leaked out after movements in and out of the cabinet, and that the use of a gas burner 'pushed' air out.…”
Section: Class II 'Safety Cabinet'mentioning
confidence: 99%
“…1979) to define constructional and performance requirements for these devices. In the period up to the introduction of this Standard a number of investigations indicated that many commercial open-fronted cabinets did not provide adequate protection to the operator (Clark & Mullan 1978;Newsom 1979u, b). Until now it has been customary for manufacturers to evaluate the performance of safety cabinets from the results of airflow and smoke visualization tests alone.…”
mentioning
confidence: 99%